Vacuum-assisted breast biopsies (VAB) carried out on an open 1.0 T MR imager: Influence of patient and target characteristics on the procedural and clinical results. Issue 6 (June 2016) - Krug, Barbara; Hellmich, Martin; Ulhaas, Angela; Krämer, Stefan; Rhiem, Kerstin; Zarghooni, Verena; Püsken, Michael; Schwabe, Hendrik; Grinstein, Olga; Markiefka, Birgid; Maintz, David
Abstract: Purpose: The study was conducted in order to assess the clinical impact of MRI-guided vacuum-assisted breast biopsies carried out using an open 1.0 T open MRI-system. Material and methods: The clinical, imaging, interventional and histological data of all 132 patients with a first MRI-guided vacuum-assisted breast biopsy carried out between 07/2005 and 03/2012 at the Radiological Department were extracted from the clinical files. The clinical outcome of patients with benign histological findings was assessed based on the clinical files and queries of the local gynecologists in charge. In the 103 interventional image data sets available target localization and target size were evaluated by two board-certified senior radiologists. Clinical data, lesion characteristics and interventional results were evaluated statistically using subgroup analyses. Results: 131 of 132 MRI-guided breast biopsies (99.2%) were carried out successfully. The median interventional duration was 30 min (25%-percentile 25 min, 75%-percentile 35 min, maximum 75 min). Minor complications occurred in 12 interventions of the 131 (9.2%). The histological work-up of the biopsy specimen showed benign results in 98 of 131 interventions (74.8%), lesions with uncertain biological potential in 5 biopsies (3.8%) and malignant findings in 28 biopsies (21.4%). There were 2 false negative histological findings. Neither the patient age nor the medical history nor the anticipated risk of developing breast cancer had an impact on the success rates and the complication rates. In the 103 interventions with available image data sets the maximum target lesion diameters were 1–5 mm in 16 lesions (15.5%), 6–10 mm in 41 lesions (39.8%) and 11–15 mm in 29 lesions (28.2%). There was a positive correlation between the maximum diameters and the rate of malignancy of the target lesions (p = 0.020) as well as a trend towards longer interventional procedure durations in smaller target lesions (p = 0.183). Conclusion: MRI-guided vacuum-assisted breast biopsy for suspicious breast lesions is a clinically safe and feasible method even in small target lesions when using an open high-field MRI-system.